2013
DOI: 10.1155/2013/312747
|View full text |Cite
|
Sign up to set email alerts
|

Silver Nanoparticles and Mitochondrial Interaction

Abstract: Nanotechnology has gone through a period of rapid growth, thus leading to the constant increase in the application of engineered nanomaterials in daily life. Several different types of nanoparticles have been engineered to be employed in a wide array of applications due to their high surface to volume ratio that leads to unique physical and chemical properties. So far, silver nanoparticles (AgNps) have been used in many more different medical devices than any other nanomaterial, mainly due to their antimicrobi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
51
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 94 publications
(55 citation statements)
references
References 28 publications
1
51
0
3
Order By: Relevance
“…100] and calcium sequestration. 101,102 To date, a small number of studies have investigated direct mitochondrial uptake of AgNPs, 45,103,104 and a subset of these studies have found evidence of AgNP entry into the mitochondrion. 45,103 The magnitude of AgNP exposure resulting in mitochondria-specific dysfunction (such as decreased ATP production, observed in fibroblasts and glioblastoma 103 and oral squamous carcinoma cells 81 ) in the cell as a whole varies and is dependent upon factors such as the rate of cellular turnover and age of the organism.…”
Section: Discussionmentioning
confidence: 99%
“…100] and calcium sequestration. 101,102 To date, a small number of studies have investigated direct mitochondrial uptake of AgNPs, 45,103,104 and a subset of these studies have found evidence of AgNP entry into the mitochondrion. 45,103 The magnitude of AgNP exposure resulting in mitochondria-specific dysfunction (such as decreased ATP production, observed in fibroblasts and glioblastoma 103 and oral squamous carcinoma cells 81 ) in the cell as a whole varies and is dependent upon factors such as the rate of cellular turnover and age of the organism.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study on patients with burns showed that fibroblasts deep under burned skin could have nAg uptake released from Acticoat (a nanocrystalline silver dressing), and nAg was located close to the outer membrane of mitochondria. 55 Mitochondrial disruption includes reduction of the membrane potential and subsequent disorders of the oxidationÀreduction system linked to energy metabolism. To this end, we closely looked at alterations of mitochondrial membrane potential.…”
Section: Articlementioning
confidence: 99%
“…They have been associated with increased adherence to bacterial cell wall, increasing membrane permeability and subsequently bacterial death (17,21). AgNP enhance the release of silver ions, affecting the bacterial respiratory chain because of reactive oxygen species (ROS) and reactive nitrogen species (RNS) production (22,23) which leads to cell damage and finally apoptosis (13). AgNP also affect bacterial DNA and RNA through denaturation and hamper bacterial replication process (24,25).…”
Section: Introductionmentioning
confidence: 99%